Redistribution of membrane-bound and cytosolic action in rabbit polymorphonuclear leucocytes during phagocytosis. - Stewart, D I (1985)
In the analysis of highly purified surface membrane from both resting and phagocytosing neutrophils an increase in the surface membrane associated actin has been demonstrated. This change at the cell periphery is associated with a coincident increase in the F-actin content of the cells following stimulation of the cells by exposure to opsonized Oil Red O droplets. The actin which is newly associated with the surface membrane of the phagocytosing cells was more susceptible to removal by detergent than the membrane-associated actin in resting cells and it was also noted that the F-actin associated with phagosomes was readily disrupted by detergent. A redistribution of the surface membrane glycoprotein 5'-nucleotidase was observed during phagocytosis, but no change in distribution of a 125I-labelled Lens culinaris lectin was observed during the entire phagocytic process.